IDNLearn.com: Where your questions meet expert advice and community support. Get step-by-step guidance for all your technical questions from our dedicated community members.
Sagot :
Let's work through the problem step-by-step.
1. Base Case: Assume the statement is true for some [tex]\( n = k \)[/tex].
Let [tex]\( d(k) \)[/tex] represent the number of dots when [tex]\( n = k \)[/tex].
2. Inductive Step: We need to prove that if the statement holds for [tex]\( n = k \)[/tex], then it must also hold for [tex]\( n = k+1 \)[/tex].
According to our assumption, [tex]\( d(k) \)[/tex] is the total number of dots when [tex]\( n = k \)[/tex].
3. Incrementing [tex]\( n \)[/tex]: Suppose we increase [tex]\( n \)[/tex] by 1, that is, we examine the case [tex]\( n = k+1 \)[/tex].
4. Expression for [tex]\( n = k+1 \)[/tex]: When [tex]\( n \)[/tex] becomes [tex]\( k + 1 \)[/tex], it means we are adding an additional level with [tex]\( k + 1 \)[/tex] dots to our total dot count.
5. Inductive Hypothesis: We assume
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
Here, [tex]\( d(k) \)[/tex] is the number of dots if [tex]\( n = k \)[/tex] and adding [tex]\( k + 1 \)[/tex] dots for the next level.
6. Combining Information:
Let’s denote the number of dots at [tex]\( n = k+1 \)[/tex] by [tex]\( d(k+1) \)[/tex]. According to our induction step, we have:
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
This shows that the number of dots for [tex]\( n = k+1 \)[/tex] is built on the number of dots for [tex]\( n = k \)[/tex] by adding [tex]\( k+1 \)[/tex] more dots.
7. Conclusion:
We’ve shown that if the statement holds for [tex]\( n = k \)[/tex], i.e., [tex]\( d(k) \)[/tex] dots, then it also holds for [tex]\( n = k+1 \)[/tex], i.e., [tex]\( d(k+1) = d(k) + (k + 1) \)[/tex].
By mathematical induction, since the statement is true for [tex]\( n=k \)[/tex] and leads directly to being true for [tex]\( n=k+1 \)[/tex], we conclude that the statement is true for all natural numbers [tex]\( n \)[/tex].
1. Base Case: Assume the statement is true for some [tex]\( n = k \)[/tex].
Let [tex]\( d(k) \)[/tex] represent the number of dots when [tex]\( n = k \)[/tex].
2. Inductive Step: We need to prove that if the statement holds for [tex]\( n = k \)[/tex], then it must also hold for [tex]\( n = k+1 \)[/tex].
According to our assumption, [tex]\( d(k) \)[/tex] is the total number of dots when [tex]\( n = k \)[/tex].
3. Incrementing [tex]\( n \)[/tex]: Suppose we increase [tex]\( n \)[/tex] by 1, that is, we examine the case [tex]\( n = k+1 \)[/tex].
4. Expression for [tex]\( n = k+1 \)[/tex]: When [tex]\( n \)[/tex] becomes [tex]\( k + 1 \)[/tex], it means we are adding an additional level with [tex]\( k + 1 \)[/tex] dots to our total dot count.
5. Inductive Hypothesis: We assume
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
Here, [tex]\( d(k) \)[/tex] is the number of dots if [tex]\( n = k \)[/tex] and adding [tex]\( k + 1 \)[/tex] dots for the next level.
6. Combining Information:
Let’s denote the number of dots at [tex]\( n = k+1 \)[/tex] by [tex]\( d(k+1) \)[/tex]. According to our induction step, we have:
[tex]\[ d(k+1) = d(k) + (k + 1) \][/tex]
This shows that the number of dots for [tex]\( n = k+1 \)[/tex] is built on the number of dots for [tex]\( n = k \)[/tex] by adding [tex]\( k+1 \)[/tex] more dots.
7. Conclusion:
We’ve shown that if the statement holds for [tex]\( n = k \)[/tex], i.e., [tex]\( d(k) \)[/tex] dots, then it also holds for [tex]\( n = k+1 \)[/tex], i.e., [tex]\( d(k+1) = d(k) + (k + 1) \)[/tex].
By mathematical induction, since the statement is true for [tex]\( n=k \)[/tex] and leads directly to being true for [tex]\( n=k+1 \)[/tex], we conclude that the statement is true for all natural numbers [tex]\( n \)[/tex].
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com has the answers you need. Thank you for visiting, and we look forward to helping you again soon.